Policies and performance of Ethiopian cereal markets - Rashid, Shahidur; Negassa, Asfaw (International Food Policy Research Institute, 2011)
Cereal production and marketing is the single largest sub-sector within Ethiopia's agriculture. It dominates in terms of its share in rural employment, agricultural land use, and calorie intake, as well as its contribution to national income. The sub-sector accounts for roughly 60 percent of rural employments, about 73 percent of total cultivated land, more than 40 percent of a typical household's food expenditure, and more than 60 percent of total caloric intake of a typical household in the country.1 The contribution of cereals to national income is also large: according to available estimates, cereals' contribution to agricultural value added is 65 percent (Diao et al. 2007), which translates to about 30 percent of GDP.2. Thus, it is no surprise that, despite differing political ideologies, all agricultural production and marketing policies since the 1960s have had a focus on the cereals sub-sector. Since 1991, strategies for both growth and poverty reduction have placed a heavy emphasis on cereal production and marketing. The Agricultural Development Led Industrialization (ADLI) strategy, the Sustainable Development and Poverty Reduction Plan (SDPRP), and the Plan for Accelerated and Sustained Development to End Poverty (PASDEP) all highlight the importance of cereals in Ethiopia's overall economic development. The Government of Ethiopia (GoE) instituted the Participatory Demonstration and Extension Training System (PADETS), in the mid-1990s with the specific purpose of increasing cereal production through demonstration of seed-fertilizer technology. As part of these strategies, the Government of Ethiopia (GoE) has undertaken substantial market reforms, accelerated investments in road and communication networks, and initiated programs to increase cereal production through large-scale demonstrations of the benefits of modern seeds and greater fertilizer use. The structure of Ethiopian cereal markets has undergone massive changes since the 1960s due to dramatic shifts in government agricultural production and market policies, vast improvements in marketing infrastructure, and major increases in domestic production. This paper documents these experiences. It begins by giving a historical overview of policies that have directly or indirectly affected cereal production and marketing.